2019
DOI: 10.18203/2349-3933.ijam20195228
|View full text |Cite
|
Sign up to set email alerts
|

The study of correlation between Body Mass Index and glycemic control-HbA1c in diabetes type 2 patients

Abstract: Background: Obesity has major adverse effects on health. Obesity is associated with an increase in mortality, with a 50-100% increased risk of death from all causes compared to normal-weight individuals, mostly due to cardiovascular causes. The aim of this study was to correlate Body Mass Index (BMI) and glycaemic control (HbA1c) in type 2 Diabetic patients.Methods: In this study 100 patients of type 2 diabetic were subjected to detailed history, clinical examination, BMI, HbA1c and routine biochemical investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…16 Sisodia et al concurred and found that obesity is associated with poor glycaemic control. 17 We postulate that these finding occurred due to the type of diabetes. In our study, PLWT1DM had significantly poorer glycaemia and were taller than PLWT2DM.…”
Section: Discussionmentioning
confidence: 96%
“…16 Sisodia et al concurred and found that obesity is associated with poor glycaemic control. 17 We postulate that these finding occurred due to the type of diabetes. In our study, PLWT1DM had significantly poorer glycaemia and were taller than PLWT2DM.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of T2D has risen exponentially in recent decades as a result of lifestyle changes 19 . Obesity almost doubled worldwide between 1980 and 2008 47 . In 2008, there were over 200 million obese men and over 300 million obese women worldwide, accounting for 11% of adults 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity almost doubled worldwide between 1980 and 2008 47 . In 2008, there were over 200 million obese men and over 300 million obese women worldwide, accounting for 11% of adults 47 . Also, BMI has been linked to an increase in metabolic disorders such as T2D 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be suggested as a diagnostic principle that identifies more cases of diabetes and pre-diabetes than fasting glucose or oral glucose tolerance tests. HbA1c is a good biomarker for diabetic complications and prediction of diabetic [43] .…”
Section: Discussionmentioning
confidence: 99%